Urban Well-Being and Community Development: Investigating the Relationship Between Built Environments, Social Networks, and Quality of Life - Christina Trisnawati Setiawan; Rahaju Ningtyas (Westscience Press, 2023)
This research investigates the dynamic interplay between the built environment, social networks, and quality of life in Bandung City's urban context, with a focus on urban community wellbeing and community development. Employing a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to comprehensively explore the relationships among these factors. The findings highlight the significance of access to green spaces, transportation options, and housing quality in influencing residents' quality of life. Moreover, strong social networks emerged as a crucial catalyst for community development, fostering a sense of belonging and social support. Integrating quantitative and qualitative insights, this research provides a nuanced understanding of how the built environment and social networks intersect to shape urban community wellbeing and enhance community development. The implications of this study extend to urban planning, policy development, and community engagement strategies, guiding efforts to create more livable and inclusive urban environments in Bandung City.